2015
DOI: 10.1371/journal.pone.0129933
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Defatted Cottonseed and Soy Meal Products

Abstract: Chemical composition is critical information for product quality and exploration of new use. Hence defatted cottonseed meals from both glanded (with gossypol) and glandless (without gossypol) cotton seeds were separated into water soluble and insoluble fractions, or water soluble, alkali soluble as well as total protein isolates. The contents of gossypol, total protein and amino acids, fiber and carbohydrates, and selected macro and trace elements in these products were determined and compared with each other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 41 publications
1
57
0
Order By: Relevance
“…impurity) in protein fractions CSPw, CSPa, and CSPI. The contents of ADF, NDF, and ADL were all higher in the pilot-scale produced WCSM and CSIR than the two fractions from laboratory experiments (He et al, 2015) apparently due to the higher fiber content in the mill-produced staring material CSM. Those data also revealed that there were 17.6% and 8.4% of WCSM, and 24.6% and 10.2% of CSIR, respectively, as cellulose and hemicelluloses.…”
Section: Major Components Of Pilot Produced Cottonseed Meal Productsmentioning
confidence: 75%
See 3 more Smart Citations
“…impurity) in protein fractions CSPw, CSPa, and CSPI. The contents of ADF, NDF, and ADL were all higher in the pilot-scale produced WCSM and CSIR than the two fractions from laboratory experiments (He et al, 2015) apparently due to the higher fiber content in the mill-produced staring material CSM. Those data also revealed that there were 17.6% and 8.4% of WCSM, and 24.6% and 10.2% of CSIR, respectively, as cellulose and hemicelluloses.…”
Section: Major Components Of Pilot Produced Cottonseed Meal Productsmentioning
confidence: 75%
“…The protein content of CSPw was 64.4% which was lower than the protein content of laboratory-made CSPw (He et al, 2013a;He et al, 2015). The product CSPa was basically protein-dominated, more like the total protein isolate CSPI, which is also observed with the laboratory-made CSPa and CSPI (He et al, 2013a;He et al, 2015). Oil was an impurity (2.5%) in the staring material CSM (Table 1).…”
Section: Major Components Of Pilot Produced Cottonseed Meal Productsmentioning
confidence: 91%
See 2 more Smart Citations
“…Previous characterization of cottonseed meal products were mainly on the chemical composition (Berardi and Cherry, 1979;He et al, 2015;Zhang et al, 2009), protein structure (He et al, 2013a;2014c;King, 1980), and physicochemical properties (Grevellec et al, 2001;He et al, 2016b;Tunc and Duman, 2007;Zhou et al, 2015). Unlike several agricultural products noted above, the surface characteristics of cottonseed meal products have not been examined so far.…”
Section: Introductionmentioning
confidence: 99%